Zooplankton composition and abundance in the Laptev Sea and adjacent Nansen Basin, summer, 1993 - Ivan Kireyev (Arctic Data Center, 2014)
Zooplankton composition and distribution were investigated on the Laptev Sea shelf, over the continental slope and in the adjacent deep Nansen Basin during the joint German-Russian expedition "Arctic 93'' with RV Polarstern and Ivan Kireyev in August/September 1993. Zooplankton was collected on four latitudinal transects (H, G, F and E) across the Laptev Sea continental shelf over the shelf break into the deep eastern Nansen Basin. Sampling was carried out between September 01 and 22, 1993 during the cruise "Arctic 93" with RV Polarstern (ARK IX/4). Five depth strata from the bottom or 1500 m to the surface were sampled in vertical hauls with a multiple opening-closing net (multinet, Hydrobios, Kiel, 0.25 m2 mouth opening, 150µm mesh) in the deep and slope zone. Regular depth intervals on the outer shelf and deep stations were 0-10-25-50-100-200 m and 0-25-50-200-500-1500 m (or bottom) respectively. In the shelf zone a Multinet with mesh size of 300 µm were used to sample the layers 0-10-20-30-40 m. The samples were preserved in 4% borax-buffered formalin. Lab: All zooplankton organisms from a sample were sorted to main taxonomical groups and for copepods further to species and stage level. Numerous zooplankton organisms were counted from an aliquot (the smallest one was 1:32) of a sample, while rare organisms were counted from the whole sample. Calanus finmarchicus and C. glacialis copepodite stages IV-VI were separated by prosome length according to Tande et al. (1985): CV > 3.0 mm and females > 3.2 were determined as C. glacialis. Abundance (#/m3) and biomass (mg/m3) data are presented for each taxonomic unit. This dataset was also served by ARCOD wwwarcodiv.org. However updates in latitude and longitudes are present within this submission